Characterization of Liquids Using Electrical Properties in Microwave and Millimeter Wave Frequency Bands - Öztürk, Turgut (Springer/Plenum Publishers, 2019)
This paper describes effects of electrical properties of materials to recognize the liquids with high accuracy. The goal of this study is to quickly characterize a liquid by making accurate predictions. By interpreting the relationships between the specified properties, the forecasts have been tried to be executed about other important parameters of any liquid. However, although the effects of the important parameters are paid attention, the temperature effect is not considered, in this study. Considering the high importance of safety and security applications, the liquids analyzed in this study were chosen to be transported by one person on various trips. Two different microwave spectroscopy systems (reflectivity free space and coaxial probe measurement methods), are used to collect the electrical properties of liquids by vector network analyzer. Furthermore, these specially selected liquids are first measured in a wide frequency range and the values of their complex permittivity are given.
Keywords: Characterization of liquids; Permittivity; Conductivity; Coaxial probe; Non-destructive measurement